Choice of Remediation Technology for a Contaminated Soil by 1,2-Dichloroethane (DCA) - Luis Antonio, García Villanueva; Carlos Raúl, González Herrera; Ana Lucero, Isidro Guadalupe (Journal of Basic & Applied Sciences, 2023)
In Mexico, there are 635 sites contaminated by hazardous waste, due to the fact that a few years ago there was no legislation to support and guarantee environmental protection. This led to decades of contamination of soils and bodies of water. In the following case study, landfills were identified where 1,2-dichloroethane was stored, generating contaminated soil in this location, even affecting subway water bodies. The aim of this work is to identify the technologies for the remediation of contaminated soils, taking into account the affected site, the characteristics of the residue, costs and time, in order to determine the most effective and ideal technology. The Federal Remediation Technologies Roundtable (FRTR) will be considered as the counterpart for the selection of treatment technologies, published by the Remediation Bureau. The best technology for site remediation is "Soil Vapor Extraction", being the most ideal and efficient in terms of time and cost, and generating a high impact remediation outcome. The counterpart (FRTR) is considered to be a support tool that provides the most appropriate technologies for the remediation of a contaminated site.